Human Fetal Striatum-Derived Neural Stem (NS) Cells Differentiate to Mature Neurons In Vitro and In Vivo - Monni, Emanuela; Cusulin, Carlo; Cavallaro, Maurizio; Lindvall, Olle; Kokaia, Zaal (Current Stem Cell Research & Therapy, 2014)
Clonogenic neural stem (NS) cell lines grown in adherent cultures have previously been established from embryonic stem cells and fetal and adult CNS in rodents and from human fetal brain and spinal cord. Here we describe the isolation of a new cell line from human fetal striatum (hNS cells). These cells showed properties of NS cells in vitro such as monolayer growth, high proliferation rate and expression of radial glia markers. The hNS cells expressed an early neuronal marker while being in the proliferative state. Under appropriate conditions, the hNS cells were efficiently differentiated to neurons, and after 4 weeks about 50% of the cells were βIII tubulin positive. They also expressed the mature neuronal marker NeuN and markers of neuronal subtypes, GABA, calbindin, and DARPP32. After intrastriatal implantation into newborn rats, the hNS cells survived and many of them migrated outside the transplant core into the surrounding tissue. A high percentage of cells in the grafts expressed the neuroblast marker DCX, indicating their neurogenic potential, and some of the cells differentiated to NeuN+ mature neurons. The human fetal striatum-derived NS cell line described here should be a useful tool for studies on cell replacement strategies in models of the striatal neuronal loss occurring in Huntington’s disease and stroke.
Keywords: proliferation